2022
DOI: 10.1371/journal.pone.0269496
|View full text |Cite|
|
Sign up to set email alerts
|

The psychological impact of the COVID-19 pandemic in Portugal: The role of personality traits and emotion regulation strategies

Abstract: Recent evidence suggests that both personality traits (PT) and emotion regulation (ER) strategies play an important role in the way people cope with the COVID-19 pandemic. The aim of this study was two folded. First, to longitudinally investigate the psychological distress (depression, anxiety, and stress levels) taking in consideration PT and ER strategies in 3 different moments: during the first lockdown period (April/20), at the first deconfinement (May/20) and 1-month after the first deconfinement (Jun/20)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This finding is consistent with previous findings, indicating that emotional dysregulation moderates or is related to psychological problems in the general population, in contexts other than the COVID-19 pandemic, and in the context of the COVID-19 pandemic. [8][9][10][11][12][13][14][15] This suggests that difficulties in understanding, accepting, and managing emotions is sig-nificant for psychological problems in the context of COVID-19, similar to other traumatic events. Therefore, one target of psychological interventions that aim at the management of psychological problems may be emotional dysregulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous findings, indicating that emotional dysregulation moderates or is related to psychological problems in the general population, in contexts other than the COVID-19 pandemic, and in the context of the COVID-19 pandemic. [8][9][10][11][12][13][14][15] This suggests that difficulties in understanding, accepting, and managing emotions is sig-nificant for psychological problems in the context of COVID-19, similar to other traumatic events. Therefore, one target of psychological interventions that aim at the management of psychological problems may be emotional dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…9 Within the context of the COVID-19 pandemic, emotion regulation strategies, such as reappraisal, refocus and suppression, can predict post-traumatic stress disorder (PTSD) symptoms, stress, anxiety and depression. 10- 13 Indeed, evidence has also suggested that difficulties in regulating emotions are risk factors for psychological problems, such as depression and stress, 14 and that reappraisal and suppression are mediators in the relationship between perceived parental support and depression. 15 Previous studies have indicated that secure attachment protects against psychological problems, while insecure attachment increases the risk of psychological problems.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that contagion waves lasted throughout 2020 and 2021, protracting the emergency and resulting in mandatory periods of home confinement and social distancing. Nonetheless, few studies have been conducted to examine the emotional and psychological responses to such a prolonged crisis in its various later stages from an age- and individual-differences perspective (e.g., up to October 2020 in Maggi et al [ 30 ]; December 2020 in Carbone et al [ 1 ]; February 2021 in Kluwe-Schiavon et al [ 31 ]; July 2021 in Fields et al [ 32 ]). Although the COVID-19 pandemic has sadly created an unavoidable, prolonged global crisis, it also represents a suitable context to examine further the age-related and individual differences between young and older adults in those emotional and psychological processes likely to influence and differentiate individuals’ psychological responses to adversities, namely emotion regulation, optimism, and hope.…”
Section: Introductionmentioning
confidence: 99%